Solaredge technologies, inc. equity research - capabilities far beyond inverter technology - Holm, Mattes (2021)
This equity research values SolarEdge Technologies, Inc. and analyzes if SolarEdge can maintain its market position in a strong growing solar energy industry that recently dropped to a competitive price. The revenue forecast is based on a giga watts hipped metrics that evaluates the company’s revenue streams on a geographical and segmental level, while analyzing the revenues from the recent acquisitions. Additionally, the report evaluates SolarEdge’s capabilities beyond its core business. An analysis of the competitive environment helps determine the expected future market shares of the company. Furthermore, effects of decreasing prices, softening of subsidies, trade wars, and technological advancement are analyzed. Finally, the analysis concludes with a “BUY” recommendation. The target stock price is $409.37,and the current price is $319.12, leading to an expected return of 28.33%.